TRADE PROMOTION APPROACHES TO STRENG THEN THE INTERNATIONAL COMPETITIVENESS OF ENTERPRISES - Octavian - Liviu Olaru (Global Economic Observer)
Starting from the concept of export promotion in the new world economic context, there are presented the role and attributions of Trade Promotion Organizations, institutional structures created by UNCTAD in cooperation with WTO, implemented in many countries all over the world, Romania included, with a logistic and methodological support on behalf of the initiating organizations.Trade Promotion Organizations (TPO), governmental and non-governmental, are representing the main institutional link in the above mentioned field of activity, with a wide range of attributions in supplying the exporting companies with specialized services.